A Pharmacodynamical and Therapeutic Potential of Sthavar Visha w.r.t. Visha Guna (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda always emphasized the two aspects i.e., concept of Sukham dukham ayu or Hitam- ahitam. This Dvandaj relationship helps us to understand the concept of useful nature of Visha dravya. It’s remarkable how the Visha dravya present in nature has been utilized by the knowledge of Ayurveda to the benefit of human beings. Aim: To review the Rasapanchak of Sthavar visha with the 10 Guna of Visha mentioned in Schedule E (1) drug & Upvisha. Objective: To compare the similar Gunas of Sthavar visha with Visha guna. Material & Method: Plants mentioned in schedule E of Drugs & Cosmetic Act 1945, were studied for their Dravyaguna properties and obtained from the Dravyaguna vigyan. The rules and regulation related with poisonous drugs are given in Drugs & Cosmetic Act 1945. Relevant information related to Visha was collected from the Ayurvedic text, databases, books affiliated with Agad Tantra. Result: There are 14 drugs of plant origin mentioned in schedule E (1) along with the safety studies and packing of these drugs guidelines in drugs and cosmetic act 1945, 1 drug of animal origin and 7 drugs of mineral origin. Out of 10 Gunas of Visha 6 Gunas i.e., Laghu, Tikshna, Ruksha, Vyavayi, Vikasi and Sukshma are similar to Gunas of poisonous plants. Conclusion: Due to similarities in Visha guna there is separate category of Sthavar visha (poisonous drugs) which makes them different from other plant drugs, along with their different mode of action which is similar to action of Visha. There is a need of detailed safety studies of these drugs to make them recognizable at global health.